Implementation of the Greedy Algorithm for Optimal Police Patrol Route Search in the Jurisdiction of Semendawai Suku III Police Sector - Nandra Sari, Vingky; Sutabri, Tata (International Journal Scientific and Professional, 2025)
Police patrols represent a strategic effort to maintain public security and order. However, determining an optimal patrol route remains a challenge, particularly in ensuring time and distance efficiency. This study aims to identify the optimal police patrol route in the jurisdiction of the Semendawai Suku III Police Sector using the Greedy algorithm. This method was selected for its ability to rapidly generate solutions by choosing the most favorable option at each step. The data utilized in this research include ten villages identified as high-risk areas based on the number of criminal reports recorded in 2024, as well as inter-village distances collected through regional mapping. The application of the algorithm resulted in a total patrol distance of 121.2 kilometers, following the sequence: Police Sector (A) → Sriwangi (B) → Kerujon (C) → Karang Endah (D) → Margorejo (E) → Taman Agung (F) → Taraman (H) → Kota Tanah (I) → Melati Jaya (J) → Nirwana (K) → Karang Marga (G) → returning to the Police Sector (A). This study contributes to data driven patrol strategy management, enhancing both the efficiency and effectiveness of police operations in maintaining regional security stability.